ETIKA BISNIS DALAM ISLAM: IMPLEMENTASI PRINSIP AKHLAK DALAM TRANSAKSI MUAMALAH - Syawal Tawakkal Asdar; Dimas Adi Saputra; Ahmad Baehaki; Muhammad Ridho Azka (Media Riset Bisnis Manajemen Akuntansi, 2025)
This research aims to examine the application of business ethics in Islam, particularly moral principles in muamalah transactions, as well as the challenges faced in its implementation in the modern era. Using a descriptive qualitative approach based on a literature study, this research highlights key values such as honesty, openness, trustworthiness and responsibility as the foundation of Islamic business ethics. The case study of Toko Roti Gembul in Pontianak shows how these principles can be applied in the business world. The results also reveal various challenges, such as a lack of understanding of sharia concepts, weak supervision, and not optimal integration of Islamic values in business strategies. Al-Ghazali's thoughts on positive motivation and business as fardhu kifayah also strengthen the urgency of ethics in building a fair and sustainable economic system. This research is expected to be an academic and practical contribution in encouraging the application of Islamic values in modern business activities.Keywords: Islamic business ethics, morals, muamalah, transactions, sharia principles.